DIGITAL INHERITANCE AND LEGAL VACUUMS: IMPLICATIONS FOR LEGAL CERTAINTY IN INDONESIA - Salsabila, Saila; Sholihin, Rahmat (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
The advancement of digital technology has generated new forms of wealth known as digital assets, which possess economic value and can be inherited such as cryptocurrency wallets, monetized accounts, and cloud-based data. However, the legal system in Indonesia, both in Islamic law and in national positive law, has yet to explicitly regulate the inheritance mechanisms of these digital forms of property. This paper addresses the central issue of how digital assets are positioned within inheritance law from the perspectives of Islamic jurisprudence and Indonesian positive law, and how the absence of legal regulation affects legal certainty and the protection of heirs. This research employs a qualitative methodology with a normative and conceptual approach, incorporating the study of classical Islamic legal texts, national legislation, and global digital platform policies. The findings indicate that digital assets can be classified as māl mutaqawwim, lawfully inheritable wealth based on the objectives of Islamic law (maqāṣid al-syarīʿah), particularly within the framework of ḥifẓ al-māl (protection of property). Nonetheless, the absence of technical provisions in the Compilation of Islamic Law (KHI), the Civil Code, and the Electronic Information and Transactions Law (ITE Law) creates legal uncertainty, impeding access and execution of digital inheritance by heirs. Therefore, a responsive and adaptive legal formulation is urgently needed to ensure justice and legal certainty in the inheritance of digital assets.